Warm and out of breath: Thermal phenotypic plasticity in oxygen supply. (2nd October 2019) - Kielland, Øystein Nordeide; Bech, Claus; Einum, Sigurd
Abstract: Aquatic ectotherms face a challenge of obtaining sufficient oxygen, and it is commonly claimed that this challenge increases with increasing environmental temperature, causing concerns about the fate of aquatic ecosystems under climate change. However, the oxygen challenge hypothesis often ignores the effect of known phenotypic plastic responses. These can occur on either a within‐ or multigenerational scale, where multiple reactions act in concert to increase oxygen supply in response to increased temperature in a wide range of traits (molecular, egg content, behavioural, cell structure, morphological). Here, we combine a novel modelling approach with empirical measurements that enable quantification of how both the oxygen supply (maximum oxygen diffusion rate) and demand (metabolic rate) are affected by temperature while allowing for phenotypic plasticity. We exposed the aquatic ectotherm Daphnia magna to a range of temperatures (17–28°C) over several asexual generations and confirm that phenotypic plasticity contributes to an increased ability to obtain oxygen on the whole‐organism level at high temperatures. This response is strongest within the highest temperature range (22–28°C), where the change in oxygen challenge is expected to be most pronounced. However, the observed thermal plasticity in oxygen supply failed to compensate for the increased demand. Thus, we provide empirical evidence that the oxygen challenge in aquatic ectotherms increases with increasing temperature, even in the presence of phenotypic plasticity in oxygen supply. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.